Kuntillet ʿAjrud Inscription 4.3: A Note on the Alleged Exodus Tradition - Krause, Joachim J. (Vetus Testamentum, 2017)
It has been proposed recently to read the heavily fragmented plaster inscription 4.3 from Kuntillet ʿAjrud as an attestation of the Exodus tradition. Based on the marked differences from the comparative biblical material, far-reaching conclusions regarding the evolution of the Exodus tradition have been drawn. But the reading suffers from serious problems.